2019
DOI: 10.1038/s41598-019-54848-x
|View full text |Cite
|
Sign up to set email alerts
|

Sodium valproate and 5-aza-2′-deoxycytidine differentially modulate DNA demethylation in G1 phase-arrested and proliferative HeLa cells

Abstract: Sodium valproate/valproic acid (VPA), a histone deacetylase inhibitor, and 5-aza-2-deoxycytidine (5-aza-CdR), a DNA methyltransferase 1 (DNMT1) inhibitor, induce DNA demethylation in several cell types. In HeLa cells, although VPA leads to decreased DNA 5-methylcytosine (5mC) levels, the demethylation pathway involved in this effect is not fully understood. We investigated this process using flow cytometry, ELISA, immunocytochemistry, Western blotting and RT-qPCR in G1 phasearrested and proliferative HeLa cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
11

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 66 publications
1
22
0
11
Order By: Relevance
“…Valproic acid has also been found to induce chromatin decondensation that lasts longer than the time assigned to promote histone acetylation. This finding suggested that VPA could affect the methylation status of DNA and histones, which was confirmed in several cell types, including tumor cells (Detich et al, 2003;Milutinovic et al, 2007;Marinova et al, 2011;Palsamy et al, 2014;Rocha et al, 2019). The VPA-promoted demethylation of DNA, which leads to the conversion of 5-methylcytosine (5mC) to cytosine (C), involves a complex process flowing through an active or a passive pathway, depending on the cell type.…”
Section: Introductionmentioning
confidence: 78%
See 1 more Smart Citation
“…Valproic acid has also been found to induce chromatin decondensation that lasts longer than the time assigned to promote histone acetylation. This finding suggested that VPA could affect the methylation status of DNA and histones, which was confirmed in several cell types, including tumor cells (Detich et al, 2003;Milutinovic et al, 2007;Marinova et al, 2011;Palsamy et al, 2014;Rocha et al, 2019). The VPA-promoted demethylation of DNA, which leads to the conversion of 5-methylcytosine (5mC) to cytosine (C), involves a complex process flowing through an active or a passive pathway, depending on the cell type.…”
Section: Introductionmentioning
confidence: 78%
“…In MCF-7 human breast tumor cells, for instance, VPA-induced DNA demethylation occurs through a passive pathway (Marchion et al, 2005). In human lens epithelial cells and HeLa cells, VPA acts predominantly within the active DNA demethylation pathway, through the action of enzymes of the ten-eleven translocation (TET) protein family and independent of cell replication, although a passive pathway promoting the suppression of DNA methyltransferase (DNMT) activity may also be involved (Palsamy et al, 2014;Rocha et al, 2019). Although reversible, DNA methylation changes are more stable than histone acetylation alterations, and may lead to long-term epigenetic reprogramming (Milutinovic et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The experimental results presented in this article suggests lysine acetylation is associated with VPA attenuating MASP and C3 gene expression we cannot rule out histone deacetylation of other complement genes. Furthermore, in addition to causing histone hyperacetylation, VPA has been shown to regulate replication-independent loss of DNA methylation 72 that is consistent with elevated Tet2 DNA demethylase enzyme 73 . This seemingly extends the functional role of HDAC inhibitors such as VPA that alter lysine acetylation and deacetylation including DNA methylation by extracellular signalling mediated by hyperglycaemia 74 .…”
Section: Discussionmentioning
confidence: 90%
“…These are proposed tumour suppressor genes: with PGP9.5 able to bind and stabilise p53 by preventing its proteasomal degradation; and NMDAR2B and CCNA1 acting to facilitate apoptosis ( Waraya et al, 2015 ). The therapeutic importance of these findings is that epigenetic modifiers able to reduce methylation [e.g., 5-aza-2’-deoxycytidine (5-aza-dC), a DNA methyltransferase 1 (DNMT1) inhibitor]; in combination with sodium valproate or valproic acid [a histone deacetylase inhibitor ( Rocha et al, 2019 )], will have specific value, with greater relevant application in these male gastric cancers, due to their higher methylation incidence. Altered methylation (either 11 hyper-methylated and seven hypomethylated) of ∼30% of genes (18/67) in the p53 KEGG pathway were also found in colorectal cancer ( Molnar et al, 2018 ), which now begs for interrogation of sex differences.…”
Section: Altered Tp53 Regulation and Its Cancer Rimentioning
confidence: 99%